The Construction of Mathematical Communication Schemes Based on Learning Styles - Mohammad Archi Maulyda; Muhammad Erfan; Nourma Pramestie Wulandari; Vivi Rachmatul HIdayati; Umar Umar (Universitas Jambi, Indonesia, 2020)
The purpose of this study was to describe the construction of students’ mathematical communication in solving problems based on students’ learning styles. This research method is qualitative-descriptive. The subjects in this research were three students, each of these students are theoretical, reflective, and pragmatic learning styles. The research instrument used was mathematics problems with a topic similarity. The data obtained were in the form of students’ work and short unstructured interviews. The data were analyzed based on indicators of problem-solving and mathematical communication. The results showed that students with theoretical learning styles could communicate the entire process of the problem-solving well. Students with a reflective learning style could show a good problem-solving process. Even so, mathematical communication is not very clear. Students with a pragmatic learning style had a poor performance in solving problems. The mathematical communication is also not very good.